Human-computer interaction : recognition and interaction technologies : Thematic Area, HCI 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, proceedings, part II /: recognition and interaction technologies : Thematic Area, HCI 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, proceedings, part II. (2019) - Unknown
No abstract available